The NGS Magic Pudding: A Nanopore-Led Long-Read Genome Assembly for the Commercial Australian Freshwater Crayfish, Cherax destructor - Austin, Christopher M.; Croft, Laurence J.; Grandjean, Frederic; Gan, Han Ming (Frontiers in Genetics, 2022)
Cherax destructor, the yabby, is an iconic Australian freshwater crayfish species, which, similar to other major invertebrate groups, is grossly under-represented in genomic databases. The yabby is also the principal commercial freshwater crustacean species in Australia subject to explotation via inland fisheries and aquaculture. To address the genomics knowledge gap for this species and explore cost effective and efficient methods for genome assembly, we generated 106.8 gb of Nanopore reads and performed a long-read only assembly of the Cherax destructor genome. On a mini-server configured with an ultra-fast swap space, the de novo assembly took 131 hours (~5.5 days). Genome polishing with 126.3 gb of PCR-Free Illumina reads generated an assembled genome size of 3.3 gb (74.6% BUSCO completeness) with a contig N50 of 80,900 bp, making it the most contiguous for freshwater crayfish genome assemblies. We found an unusually large number of cellulase genes within the yabby genome which is relevant to understanding the nutritional biology, commercial feed development and ecological role of this species and crayfish more generally. These resources will be useful for genomic research on freshwater crayfish and our methods for rapid and super-efficient genome assembly will have wide application.